125k views
0 votes
Solve the following equation. Show all your work.

Start Fraction x over x minus 2 End Fraction plus Start Fraction x minus 1 over x plus 1 End Fraction equals negative 1

someone...please..god..

1 Answer

3 votes

(x)/(x - 2) + (x - 1)/(x + 1) = -1


(x - 2)(x + 1) * (x)/(x - 2) + (x - 2)(x + 1) * (x - 1)/(x + 1) = -1(x - 2)(x + 1)


(x + 1)x + (x - 2)(x - 1) = -1(x - 2)(x + 1)


x^2 + x + x^2 - 3x + 2 = -x^2 + x + 2


3x^2 - 3x = 0


3x(x - 1) = 0


x = 0~~~or~~~x - 1 = 0


x = 0 ~~~ or ~~~ x = 1


Since neither 0 nor 1 cause a zero in a denominator in the original equation, 0 and 1 are acceptable as solutions.

Answer: x = 0 or x = 1



User Jan Kratochvil
by
5.0k points